A comparison of ontology servers - Ahmad, M. Nazir; M. Colomb, Robert; Abd Wahid, Mohd. Taib (2006)
Recently, an ontology is increasingly becoming an essential tool for solving problems in many research areas. The ontology is a complex information object. It is used in practice and can contain millions of concepts in complex relationship. When we want to manage complex information objects, we generally turn to information systems technology. There are many tens of millions of information systems in use around the world doing many things ranging from helping a business manage its billing to keeping track of the design and parts inventory of large aircraft. An information system intended to manage ontology is called an ontology server. The ontology server technology is at the time of writing quite immature. Therefore, in this paper, we necessarily try to remain somewhat speculative in nature by reviewing several ontology servers in mainstream literatures. As a result, we point out some important opportunities that would trigger several research questions related to the server technology.